Development of an Active Film with Natural Zeolite as Ethylene Scavenger - Guarda-Moraga, A; Rodriguez-Mercado, F; Bruna-Bugueno, J (Sociedad Chilena de Quimica, 2014)
Ethylene (C2H4) acts as a plant hormone, growth regulator that has a number of effects on the growth. Ethylene accelerates respiration, leading to maturity and also softening and ripening of many kinds of fruits. Although ethylene has some positive effects, it is often hazardous to the quality and shelf-life of fruits and vegetables. The removal of ethylene and/or inhibition of the effect of ethylene in stored environments is fundamental to maintaining postharvest quality of climacteric produce. In this study, the efficiency of a Chilean natural zeolite (NZ-Ch) against a commercial Na+ montmorillonite (Cloisite Na+) was studied. The aluminosilicate characterization (XDR, FTIR, EGME, CEC, chemical composition) indicates that natural Chilean zeolite belongs to mordenite group. Elemental chemical analysis indicated that compensating ions, were sodium for MTNa+ and calcium, sodium and potassium for NZ-Ch, and in both aluminosilicates copper was present in their composition. Ethylene adsorption kinetics were fitted to a pseudo-second order model. The rate constant of the ethylene adsorption was nearly double for NZ-Ch compared with MtNa+. Langmuir-Freundlich isotherm allowed to determine maximum adsorption capacity that reached values of 5.4 ?l g-1 for NZ-Ch and 1.28 ?l g-1 for MtNa+. Films of low density polyethylene (LDPE) were obtained with different NZ-Ch concentrations. After 50 hours, a removal of 37% of ethylene present on headspace was achieves with 10% of ZN-Ch in LDPE active films.